Efficient optimization of pressure regulation in water distribution systems using a new-relaxed Pressure Reducing Valve model - Pham Duc Dai (Vietnam Journal of Science and Technology, 2018)
Water loss is a global problem. Water loss in leakages in water distribution systems (WDSs) can be reduced by regulation of the average excessive pressure through optimizing operations of Pressure Reducing Valves (PRVs) placed in WDSs. This optimization task can be formulated as a nonlinear program (NLP). Since the pressure settings of PRVs are control variables determining to overall pressure of the system, the PRV model should be accurate and can account all scenarios occurring in WDSs in practice. The PRV models, having been used until now, either cannot describe complete operation modes of real PRVs or is complicated. In this paper, we develop a mathematical model for PRVs capable of describing complete operation modes of PRVs in practice. In addition, we show that the PRV model equation can be relaxed so that it is useful for formulation of NLP. With the proposed PRV model, the formulated NLP can be solved by NLP algorithms based gradient methods to high quality solution and in less computation time. Two benchmarks of WDSs are taken to demonstrate the efficiency of the proposed PRV model.